Catalytic pyrolysis of used tires on noble-metal-based catalysts to obtain high-value chemicals: Reaction pathways - Osorio Vargas, Paula (2022)
A systematic study on the use of noble metals (Pd, Pt, Au) supported on titanate nanotubes (NT-Ti) for selectively producing BTX and p-cymene from waste tire pyrolysis is provided here. All the materials were characterized for chemical, textural and structural properties using a range of analytical techniques. The M/NT-Ti (M: Pd, Pt, or Au) catalysts exhibit low nanoparticle sizes (1.8 <NPs<2.2 nm), and a homogeneous pore size distribution. The catalysts demonstrated excellent activity for converting WT into BTX-enriched oil when tested in a micropyrolysis system coupled to chromatography/mass spectrometry (Py–GC/MS). The BTX production was enhanced by the presence of catalysts with a selectivity order as follows Pd > Pt ≈ Au > support > non-catalyst. The Py-GC/MS suggest that the catalysts participate in the secondary reactions of dealkylation, dehydrogenation, isomerization, aromatization, and cyclization leading to a higher formation of BTX than the uncatalyzed reaction. Finally, a comprehensive reaction pathway describing the catalytic pyrolysis of WT over Pd/NT-Ti was proposed by studying the catalytic pyrolysis of individual polymers constituting the waste tires, and D,L-Limonene.